2023
DOI: 10.1371/journal.pone.0291254
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in immune surveillance and expression of NKT and γδT cell activation markers after consuming a nutraceutical supplement containing Aloe vera gel, extracts of Poria cocos and rosemary. A randomized placebo-controlled cross-over trial

Liu Yu,
Sage McGarry,
Dina Cruickshank
et al.

Abstract: Goal To evaluate the acute impact of a nutraceutical blend on immune surveillance. Study design A randomized, double-blind, placebo-controlled, cross-over trial was conducted in 11 healthy subjects. Blood samples were taken immediately before and at 1, 2, and 3 hours after consuming placebo or 500 mg of UP360, which is a blend of botanicals from Aloe vera, Poria cocos, and rosemary (APR extract). Immunophenotyping and flow cytometry quantified numbers of monocytes, NK cells, NKT cells, CD8+ cytotoxic T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Consuming nutraceutical products represents a unique opportunity to provide rapid support for the natural processes of immune surveillance [17,26,27]. The clinical data presented here showed rapid and highly significant changes to activation markers on NK cells, where the CD25 activation marker was significantly elevated at 1 h after consuming a single dose of EG compared to placebo, suggesting increased NK cell proliferative activity [28], and possibly cytotoxic activity [29].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Consuming nutraceutical products represents a unique opportunity to provide rapid support for the natural processes of immune surveillance [17,26,27]. The clinical data presented here showed rapid and highly significant changes to activation markers on NK cells, where the CD25 activation marker was significantly elevated at 1 h after consuming a single dose of EG compared to placebo, suggesting increased NK cell proliferative activity [28], and possibly cytotoxic activity [29].…”
Section: Discussionmentioning
confidence: 68%
“…A placebo-controlled cross-over study design was used for this clinical study (clinical trial registration NCT05431751), which was conducted in accordance with the Declaration of Helsinki, and approved by the Argus Independent Review Board, Tucson, AZ, USA. The sample size was determined based on previous studies on β-glucan-rich nutritional supplements and we aimed for a minimum of 10 participants to complete the study [17]. People from the database at the study site, representing people who have previously indicated an interest in participating in clinical studies on natural products, were approached, and, if interested, were invited for screening.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A neutraceutical combination of AV, Poria cocos, and rosemary extract triggered the activation markers on various types of innate immune cells, resulting in enhanced immune surveillance and antioxidant defense [ 14 ]. In C57BL/6 mice, processed AV gel given orally functions as an adjuvant for influenza vaccinations [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%